Natural and anthropogenic barriers to climate tracking in river fishes along a mountain–plains transition zone. Issue 7 (31st May 2017) - Gibson‐Reinemer, Daniel K.; Rahel, Frank J.; Albeke, Shannon E.; Fitzpatrick, Ryan M.
Abstract: Aim: To examine how the distributions of fishes in three rivers changed over four decades of rising air temperatures. Location: Colorado, USA. Methods: We used fish sampling over more than four decades in three rivers in Colorado, USA, to examine changes in the upper and lower distribution limits of fishes. Results: There was a divergent pattern of range shifts among species. One coldwater fish species showed the expected pattern of retraction at its lower limit and expansion at its upper limit. However, warmwater fishes, on average, did not shift their upper distribution limit. Main conclusions: All three rivers displayed a strong habitat transition from upstream, high‐gradient reaches to downstream, low‐gradient reaches, suggesting that habitat conditions associated with high channel slope may limit the ability of some fish species to track warming water temperatures. In addition, potential anthropogenic barriers to fish movement occurred near species distribution limits, and these may prevent or delay range shifts in river fishes. The overall pattern of range shifts was consistent across the three rivers, suggesting a coherent influence of species' traits, physiological tolerances and habitat requirements on fish species distributions.